Studying the Yield Potential of Small Lombok Plants (Capsicum frutescense L.) Planted in Containers Due to Volume of Water Supply in Various Soil Types and Composition of Planting Media - Raden Faridz; Sri Nurholifah (Universitas Muhammadiyah Sidoarjo, 2010)
The aim of this research was to study the yield potential of Capsicum frutescence affected by difference watering volume on varies soi types and growth media compositions. This research was held at Trunojoyo University about 3 m above sea level with the average rainfall about 1685 mmper year. A transparent plastic roof was used to protect the experiment from rain. Polybags used were 40 cm x 20 cm in sized. Split plot design arranged as factorial was used in this experiment and was replicated three times. As main factor was volume of watering wiyh three levels of 0,25;0,5; 0,75; and 1,00 times of fied water capacity. The subfactors were soil types and media composition. The four levels of soil type used were regosol, vertisol, mediterane and alluvial. The three levels of media composition were proportion of soil: manure: rice husk of 1: 1: 1; 1: 2: 1; and 2: 2: 1. Result of this experiment showed that all of combination between treatments did not influence yield and yield components. But individual treatments significantly influenced the yield and some yield components. Fruit weight of 0,90; 1,02; and 0,91 g were given by watering volume of 0,75 times of field water capacity; alluvial soil type and media composition of soil: manure: rice husk (2 ; 2: 1), respectively